Black Tea Extract and Its Theaflavin Derivatives Inhibit the Growth of Periodontopathogens and Modulate Interleukin-8 and beta-Defensin Secretion in Oral Epithelial Cells - Lombardo Bedran, Telma Blanca; Morin, Marie-Pierre; Spolidorio, Denise Palomari [UNESP]; Grenier, Daniel (Public Library Science, 2015)
Over the years, several studies have brought evidence suggesting that tea polyphenols, mostly from green tea, may have oral health benefits. Since few data are available concerning the beneficial properties of black tea and its theaflavin derivatives against periodontal disease, the objective of this study was to investigate their antibacterial activity as well as their ability to modulate interleukin-8 and human beta-defensin (hBD) secretion in oral epithelial cells. Among the periodontopathogenic bacteria tested, Porphyromonas gingivalis was found to be highly susceptible to the black tea extract and theaflavins. Moreover, our data indicated that the black tea extract, theaflavin and theaflavin-3,3'-digallate can potentiate the antibacterial effect of metronidazole and tetracycline against P. gingivalis. Using lipopolysaccharide-stimulated oral epithelial cells, the black tea extract (100 mu g/ml), as well as theaflavin and theaflavin-3,3'-digallate (50 mu g/ml) reduced interleukin-8 (IL-8) secretion by 85%, 79%, and 86%, respectively, thus suggesting an anti-inflammatory property. The ability of the black tea extract and its theaflavin derivatives to induce the secretion of the antimicrobial peptides hBD-1, hBD-2 and hBD-4 by oral epithelial cells was then evaluated. Our results showed that the black tea extract as well as theaflavin-3,3'-digallate were able to increase the secretion of the three hBDs. In conclusion, the ability of a black tea extract and theaflavins to exert antibacterial activity against major periodontopathogens, to attenuate the secretion of IL-8, and to induce hBD secretion in oral epithelial cells suggest that these components may have a beneficial effect against periodontal disease.